Assessment of vitamins and minerals content in the diets of preschool children - Suliga, Edyta; Cieśla, Elżbieta; Pietraszkiewicz, Magdalena Joanna (Journal of Education, Health and Sport, 2018)
Introduction. A proper, varied diet is indispensable to ensure the correct growth and development of children. Nutrition of this period of life also affects health status in adulthood. Evaluation of nutritional status in this vulnerable group can provide significant information, some of which will be applicable to the entire community. Findings can provide suggestions for measures that can be instituted to alleviate the problems observed and to improve nutritional status.AimTo assess the intake of selected vitamins and minerals by preschool-age children.Material & methods The study population comprised 102 children aged 4 years (46 girls and 56 boys). The intake of vitamins and minerals was assessed by using the 24-h dietary recall for 3 days. The results were compared with the Polish EAR and AI levels. Results.Total calcium and vitamin D, as well as vitamin E intakes did not meet the Estimated Average Requirements (EAR) among both groups of children. The mean intake of calcium values 10%, vitamin D 72% and vitamin E 75% of EAR respectively. Also the water intake was insufficient according to EAR.ConclusionStudy confirmed that diets of preschool children, in context of vitamin and mineral contents, need urgent modification to prevent many chronic diseases related to diet in the future.